The Protective Effect of Tropical Fruit Juice on Histopathological of Kidney Wistar Rats After Exposed Cigarette Smoke - Novi Febrianti; Haris Setiawan; Rahmat Krestianto (Universitas Ahmad Dahlan, 2020)
Cigarette smoke is a toxic compound that can interfere with physiological effects and damage the organ systems in the body. The effects of free radicals arising from cigarette smoke can be neutralized by consuming antioxidant compounds. The research aims to look at the protective effects of mixed juice from tropical fruits that grow in Indonesia to the histopathological picture of the kidney of wistar rats exposed to cigarette smoke. There were 35 rats used and divided into 5 treatment groups consisting of K (without treatment), K- (cigarette smoke exposed), P1 (strawberry and guava juice mixed juice 3ml), P2 (strawberry and papaya mixed juice 3ml), P3 (P3 (strawberry and apple mixed juice 3ml). In P1, P2 and P3 before being given a mixture of fruit juice, rats were exposed to cigarette smoke first. The treatment was carried out for 40 days by oral gavage, then on the 41st day the rats were dissected and their kidney organs were taken for observation and histopathological preparations. Histopathology preparations were made by the paraffin method and Haematoxylin Eosin staining. The cell damage data is then analyzed by comparing the kidney cells from the control group with the treatment group and scoring damage followed by the percentage of kidney damage. Data were statistically tested using ANOVA followed by Post Hoc LSD. The results showed that mixed tropical fruit juice could protect kidney cell damage by decreasing the percentage of hydropic degeneration, necrosis and infiltration of inflammatory cells compared with negative controls (P <0.05). There is no significant difference between P1, P2 and P3 in reducing cell damage. The conclusion of the study is that all combinations of tropical fruit juice can protect cell damage caused by free radicals from exposure to cigarette smoke in wistar rats.